Strategi Pengembangan Karunia Melayani Dan Memimpin Dalam Gereja Lokal Pada Generasi Z Di Era Digital - Joni Manumpak Parulian Gultom (Sekolah Tinggi Teologi Ekumene Jakarta., 2022)
The manifestation of the gift of the Holy Spirit in the early church demonstrates the capacity of supernatural power and work in the midst of the community of believers. However, according to time, especially in the development of technology, science and social media in the church, the tendency of today's ministry is more about the number of congregations, physical and financial development. The Church tends to weaken in the development of the gift of the Holy Spirit to the laity especially in generation Z. The Church has not only lost momentum in reaching out and making disciples, but has also stagnated in developing the capacity of the gifts of the Holy Spirit for the sucked Generation Z. The purpose of the study was to explain the strategies used in the development of the gift of the Holy Spirit to generation Z in the local church in the digital age. If the church does not have a clear strategy for developing the gift of the Holy Spirit to them, it will lose the spirit of evangelism, the manifestation of God's power and spiritual maturity amid disruptive technology. Research method with a descriptive qualitative approach. The construction of research in establishing mechanisms for the development of this gift relates to [1] The emphasis of teaching to Gen Z is widely underestimated. [2] Mechanisms for developing their leadership gifts from the beginning, [3] Methods relating to the provision of space and responsibility, and [4] Patterns of worship and service in the balanced use of technology.